THE IMPACT OF PARENTAL ECONOMIC CHALLENGES ON WOMEN'S EDUCATION IN INDIA - Purna Laxmi Jamatia (CV. Radja Publika, 2023)
The extent of parental economic challenges faced by women in India has significant implications for their educational opportunities. Women in India often encounter numerous obstacles due to economic factors that hinder their ability to pursue education. Gender disparities in employment opportunities and income levels create an unfavorable environment for women, affecting their access to quality education. Limited financial resources and unequal pay contribute to the economic challenges faced by women. These challenges, coupled with cultural norms and societal expectations that prioritize women's roles as caregivers and homemakers, result in limited investment in girls' education. Additionally, the burden of domestic responsibilities falls disproportionately on women, further limiting their ability to pursue education. The consequences of these challenges are far-reaching, leading to increased dropout rates, delayed education, and limited educational choices for women. Addressing these challenges requires comprehensive efforts, including financial assistance, awareness campaigns, improving access to quality education, addressing domestic responsibilities, and promoting skill development. By implementing these strategies and interventions, India can mitigate the impact of parental economic challenges on women's education, promote equal educational opportunities, and empower women to pursue their educational aspirations.